Keterampilan Literasi Informasi Pada Mahasiwa Prodi Ilmu Perpustakaan Di Universitas Terbuka Berdasarkan Standard Association Of College Reseach Libraries (ACRL) - Mustika Diana; Teguh teguh; Alpin Herman Saputra (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The research is aimed to know the literacy skill of open university library science student. This is a descriptive research with sample of open university library science student as many as 910 student among 6063 students. Tested by using the rate value. The results showed that the information literacy skills of the students of the open university library science study program were skilled. With the following details: (1) the ability of students to determine the rerequired information needs with an average score of 2.85 is included inte skilled category. (2) the ability of students to find the information needed effectively and efficiently with and average score of 2.77 skilled category. (3) evaluation of information and sources criticall with an average score of 2.71 in the skilled category. (4) capability of using the information to accomplish particular purposes with an average score of 2.77 in the skilled category. (5) understanding economic, legal, and and social aspects which are related the use of information with an average score of 2.84 in the skilled category. The researcher’s suggestion from the result of the research found is necessary to improve students’ information literacy skill to develop students’ literacy skills so that they can complete various tasks that are well received.